1997
DOI: 10.1080/07315724.1997.10718666
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate absorption from one serving of fruit juice in young children: age and carbohydrate composition effects.

Abstract: The data show that the efficiency of carbohydrate absorption of one age-specific serving of juice increases with advancing age of children. Decreased carbohydrate absorption occurs more often after ingestion of juices that contain more sorbitol, a nonabsorbable sugar and higher concentrations of fructose over glucose than after ingestion of juices which lack sorbitol and contain equal amounts of fructose and glucose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 42 publications
1
46
0
Order By: Relevance
“…These positive attributes of sorbitol can be offset by the negative side effects of its excessive use as a sugar substitute. Natural products rich in sorbitol or sorbitol-modified products have induced both decreased carbohydrate absorption and gastrointestinal problems (Nobigrot et al, 1997;Wang & van-Eys, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…These positive attributes of sorbitol can be offset by the negative side effects of its excessive use as a sugar substitute. Natural products rich in sorbitol or sorbitol-modified products have induced both decreased carbohydrate absorption and gastrointestinal problems (Nobigrot et al, 1997;Wang & van-Eys, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…13 Clinical studies have shown this process, with more apparent malabsorption when fructose concentration exceeds that of glucose (eg, apple and pear juice) than when the 2 sugars are present in equal concentrations (eg, white grape juice). 14,15 However, when provided in appropriate amounts (10 mL/kg body weight), these different juices are absorbed equally as well. 16 Sorbitol, found in small amounts in pears, apples, cherries, apricots, and plums and in sugar-free foods (eg, candy, gum, drinks, ice cream) and some liquid medications, is absorbed via passive diffusion at slow rates, resulting in much of the ingested sorbitol being unabsorbed.…”
Section: Absorption Of Carbohydrate From Juicementioning
confidence: 99%
“…Consumption of honey and fruit juice containing much fructose elicit marked increases in breath hydrogen (a marker of carbohydrate malabsorption) in children less than 1 yr of age, but not in those 2 or more yr old, suggesting fructose-induced intestinal malabsorption in very young humans possibly expressing low GLUT5 levels (116). Fructose malabsorption in 5-mo-old infants is associated with infantile colic (46) and increases their energy requirements (150).…”
Section: Physiology and Functionmentioning
confidence: 99%